The Implementation of Amil Zakat Education in Sekolah Amil Indonesia - Ade Salamun; Didin Hafidhuddin; Akhmad Alim; E Bahruddin (International Journal of Science Education and Cultural Studies, 2023)
This article aims to find out the implementation of amil zakat education at the Sekolah Amil Indonesia. This article was created using is a case study method at the Sekolah Amil Indonesia (SAI) with a qualitative approach. Data was collected by means of in-depth interviews using a guideline of questions. The data that has been collected will be analyzed using content analysis. The results of the study indicate that the basis for the establishment of SAI is that amil zakat in Indonesia must be competent. SAI was established with the aim of ensuring that amil zakat competencies are identified, developed and certified so that they have an entity in Indonesia. The SAI curriculum design refers to SKKNI, but SAI formulates its own curriculum, materials and methods for learning. There is no special character education learning material in SAI, but it is still integrated into the learning material. The learning method at SAI is currently carried out online, offline and hybrid. Learning materials are delivered in a classical way (lectures), presentations, discussions, simulations/case studies, assignments, and going to the field. Measuring the success of learning outcomes is carried out through pretest, posttest, and assignments that must rely on the certification aspect.